(untitled) (International Journal of Medical and Surgical Sciences, 2018)
Overuse of antidiabetic medications is the most common cause of hypoglycemia in diabetic subjects. Here, we report a case of hypoglycemia associated with sulfonylurea administration. An 83-year-old female patient was admitted to the emergency department with complaints of loss of consciousness and fainting. The patient’s blood glucose level was of 33 mg/dL, and she received emergency treatment with an intravenous 10% dextrose solution. In conclusion, sulfonylureas in combination with antidiabetic therapy increase the risk of hypoglycemic events in elderly patients with renal failure. Therefore, we suggest that physicians should closely monitor these patients for hypoglycemia and, preferably, use drugs that have less hypoglycemia side effects.